Diet and Anthropometrics of Children With Inflammatory Bowel Disease: A Comparison With the General Population. Issue 8 (25th April 2018) - Diederen, Kay; Krom, Hilde; Koole, Jeffrey C D; Benninga, Marc A; Kindermann, Angelika
Abstract: Background: There is a lack of knowledge regarding the diet of children with inflammatory bowel disease (IBD). Therefore, we investigated dietary intake in pediatric IBD compared to the general population and assessed anthropometrics and food avoidance. Methods: In this cross-sectional cohort study, patients younger than 18 years with IBD were included (2014−2017). Dietary intake (total energy, macro nutrients, food types) was assessed using a Food Frequency Questionnaire (FFQ) and compared with a matched reference population (n = 306). Results: There were 102 patients included (55% male, median age 15.0 years). Median height Z-score was −0.39 (interquartile range [IQR]: −1.17 to 0.26). Growth failure (height Z-scores<−1.64) was present in 11% of patients. Median BMI Z-score was 0.36 (IQR: −0.70 to 0.96). Acute malnutrition (weight-for-height Z-score<−2) was present in 3% of patients. Energy intake was lower in pediatric IBD compared to the reference population (mean kilojoule/day: 8286 vs 9794, P < 0.001). Protein intake did not differ, while fat intake was higher in pediatric IBD (mean gram/day: 101 vs 91, P < 0.001), with higher intake of vegetable oils/fats. Carbohydrate intake was lower in pediatric IBD (mean gram/day: 267 vs 305, P < 0.001), with lower intake of food types high in sugar. Food avoidance was reported in 53% of patients, with frequent avoidance of spicy (46%), high-fat food (30%), and dairy (30%). Conclusions: The diet of children with IBD differs from the general pediatric population, with lower energy intake and high rates of food avoidance. Evaluation of the dietary intake alongside anthropometrics may be important to prevent nutrition deficiencies and promote health.